Kinematic characteristics of elbow joint range of motion in elite Chinese freestyle swimmers with elbow pain during dry-land simulations of swimming strokes - Li, W.; Hadizadeh, M.; Yusof, A.; Naharudin, M. N. (Journal of Sports Sciences, 2024)
The aim of this study was to obtain quantitative data on elbow joint ROM in elite freestyle swimmers with EP in China. Of the 50 elite freestyle swimmers recruited, 41 completed all measurements during dry-land swimming stroke simulations. Elbow joint angle, velocity, and acceleration were measured using inertial measurement units. The RMSE/D was calculated to determine the elbow joint ROM deviation. Joint angle (3.33 °-42.96 °), angular velocity (-364.15 to 245.69 °/s), and angular acceleration (-7051.80 to 1465.35 °/s^2) were significantly different betwen the critical pain and healthy. The probability distributions of joint angle (15.47 ° ±14.54 °), angular velocity (2.41 ° ±111.06 °/s), and angular acceleration (1.93 ± 2222.6 °/s^2) in the slight pain group were significantly different betweenhealthy and critical pain. The RMSE/D distributions of angular velocity (28.3%) and acceleration (21.48%) in the critical pain deviated from the healthy. The peak value-RMSE/D matrix model obtained proved that elbow ROM significantly differed between the elite freestyle swimmers with EP and the healthy. Angular velocity and acceleration indicate the weakness and negative influence of kinematics on patients with EP. Thus, Potential solutions are to constantly optimise freestyle swimming techniques and strengthen the arm muscles.